Nutrition: The position in English to-day - M'Gonigle, G. C. M. (George Cuthberth Mura), -1939 (London : Industrial Christian Fellowship)
1936-11 1936 1930s 15 pages growth, condition and function attributable to qualitative defects in the diet. Such defects are very very common, and it may be said, therefore, with truth that a large proportion of our population is mal-nourished. Defective nutrition is the causal factor in such conditions as rickets and dental decay. Both these conditions can be prevented by correct feeding, and their presence is indicative of there having occurred, during the formation of bones and teeth, a shortage of the necessary food elements for the formation of hard bones and sound teeth. Examination of the elementary school children of this country shows that approximately 70% is in need of dental treatment for dental decay, and careful investigations have shown that almost as many have demonstrable signs of mild rickets. Dental decay may cause much suffering and also illness, rickets when very severe may cripple the individual (though severe cases of deformity due to this state are now rare), but minor degrees of the condition do cause some, it may be slight, change in shape of the bones. Slight changes in the shape of certain bones in girls may, and often do, give rise to serious difficulty in child birth, and cause much child mortality, maternal injury and even death. Many other conditions, some of them serious, are originated by defective feeding. Resistance to such conditions as bronchitis is so influenced; intestinal and gastric disorders and other states of ill-health are similarly produced. It is a well-established custom to give cod-liver oil to children; this practice is scientifically correct for the oil contains the valuable vitamins A and D. Vitamin A is closely associated with the resistance of the body to infection, and Vitamin D takes a great part in the prevention of rickets and of dental decay. Sailors in sailing ships suffered from 7 15X/2/217/2